Metal-poor stars towards the Galactic bulge: a population potpourri - Koch-Hansen, Andreas; McWilliam, Andrew; Preston, George W.; Thompson, Ian B. (Astronomy and astrophysics, 2016)
We present a comprehensive chemical abundance analysis of five red giants and two horizontal branch (HB) stars towards the southern edge of the Galactic bulge, at (l, b) ~ (0°,−11°). Based on high-resolution spectroscopy obtained with the Magellan/MIKE spectrograph, we derived up to 23 chemical element abundances and identify a mixed bag of stars, representing various populations in the central regions of the Galaxy. Although cosmological simulations predict that the inner Galaxy was host to the first stars in the Universe, we see no chemical evidence of the ensuing massive supernova explosions: all of our targets exhibit halo-like, solar [Sc/Fe] ratios, which is in contrast to the low values predicted from Population III nucleosynthesis. One of the targets is a CEMP-s star at [Fe/H] = −2.52 dex, and another target is a moderately metal-poor ([Fe/H] = −1.53 dex) CH star with strong enrichment in s-process elements (e.g., [Ba/Fe] = 1.35). These individuals provide the first contenders of these classes of stars towards the bulge. Four of the carbon-normal stars exhibit abundance patterns reminiscent of halo star across a metallicity range spanning −2.0 to −2.6 dex, i.e., enhanced α-elements and solar Fe-peak and neutron-capture elements, and the remaining one is a regular metal-rich bulge giant. The position, distance, and radial velocity of one of the metal-poor HB stars coincides with simulations of the old trailing arm of the disrupted Sagittarius dwarf galaxy. While their highly uncertain proper motions prohibit a clear kinematic separation, the stars’ chemical abundances and distances suggest that these metal-poor candidates, albeit located towards the bulge, are not of the bulge, but rather inner halo stars on orbits that make them pass through the central regions. Thus, we caution similar claims of detections of metal-poor stars as true habitants of the bulge.
Gesehen am 28.04.2020